Repercussions of the COVID-19 pandemic on the lives of Brazilian pregnant women (Research, Society and Development, 2022)
Qualitative study that aimed to analyze the repercussions of the COVID-19 pandemic on the lives of Brazilian pregnant women who were undergoing prenatal care from July 7 to August 15, 2020. Data were collected via Internet in a form built in REDCap and, later, organized and analyzed with the support of the Nvivo® software version release 1.6. The responses of a sample of 450 women constituted three thematic categories that reflected repercussions on emotional, family, and social, professional, and financial lives, continuously interconnected, because in addition to the changes in life and feelings inherent to the pregnancy process, there was a marked presence of feelings such as anxiety and fear, accompanied by a threat to rights related to the labor sphere, as well as work overload. It´s concluded that the COVID-19 pandemic generated mostly negative repercussions on the lives and health of pregnant women, which requires a careful look by health professionals to mitigate them in times of epidemic outbreaks or even new pandemics or endemic diseases. A new way of caring for women, preventing them from preventing infections and demystifying myths, should help to reduce the burden of emotional, family, social and professional problems during pregnancy.